A comparison of the Monospot with the Paul-Bunnell test in infectious mononucleosis and other diseases. Issue 3 (May 1969) - Seitanidis, B.
Abstract : The Monospot is a spot test designed for the diagnosis of infectious mononucleosis and its efficacy has been compared with that of the standard Paul-Bunnell test. Three out of 210 (1·4%) sera from normal persons and persons suffering from diseases other than infectious mononucleosis gave `false' positive results when compared with the Paul-Bunnell test. Using 38 sera from patients with strong clinical and haematological evidence of infectious mononucleosis no false negative results were found with the Monospot test. The sera of 37 patients gave positive results with the Paul-Bunnell test: the one negative result was positive using serum taken a few days later.